A social work study on family patterns and child abuse - Mohammad Reza Iravani; Hossein Ebrahimzadeh Asmin; Shahram Basity; Seyed Mohsen Khalifeh Soltani (Management Science Letters)
This paper presents a social work study on relationship between different family characteristics and child abuse in city of Jarghooye located in province of Esfahan, Iran. The proposed study selects a sample of 50 people and using some statistical tests verifies the effects of three factors including family income, family educational background and family size on child abuse. The results indicate that while there were some meaningful relationships between family income and family educational background, there was not any statistical evidence to believe on such relationship between family size and child abuse.